From Riding to Driving: the Effects of the COVID-19 Pandemic on Public Transit in Metro Vancouver - Bogdan Kapatsila; Emily Grisé; Dea van Lierop; Francisco J. Bahamonde-Birke (Findings)
This study analyzed a panel-based dataset to understand the effect of COVID-19 on transport behavior in Metro Vancouver, Canada, between December 2020 and May 2021. Findings from the sample indicate a decline in transit users compared to pre-pandemic levels and an increase in car use. On the other hand, we saw a shift to a more positive perception of transit in May 2021, while also capturing an increase in perceived levels of crowding. The study underscores the necessity for transit agencies to focus on instilling the feeling of safety among the population, as the majority of those who have not used transit since the beginning of the pandemic reported their willingness to return only with widespread vaccination, community immunity, or other broad successful treatments.